Vocabulary of Hatred in Social Media : An Example from Italian - Dyda, Anna; Paleta, Alicja (Neuphilologische Mitteilungen, 2023)
The study focuses on Facebook, one of the most popular social networking sites in our time, given its position in the digital world and the importance of the verbal component in it. The main objective of the research is to investigate whether in a corpus of utterances in Italian coming from two public Facebook groups, the incitement to hatred man- ifests itself through the use of slurs, the choice of which is delimited by precise criteria. The presence of the selected words is verified through automatic searches with the tools available on Facebook. Moreover, the analysis is aimed at discovering whether slurs always carry their deni- gratory potential, or whether they can also have a non-denigratory use. Some possible extensions of the research will also be defined.